Pengaruh Beban Kerja dan Insentif terhadap Kinerja Karyawan pada PT. Bank Sumsel Babel Cabang Pembantu Lemabang - Masayu, Savira Amalia Putri; Zunaidah, Zunaidah; Wita, Farla WK (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted to further understand the impact that workload and incentives have on employee performance at PT Bank Sumsel Babel Lemabang Sub-Branch. The population used as a research measurement is the employees of PT Bank Sumsel Babel Lemabang Sub-Branch as a whole which amounted to 35 people. The sample used in this study was 35 respondents using the census sampling technique. Data collected through questionnaires were analyzed by validity test, reliability test, multiple linear regression analysis, normality test, multicollinearity test, heteroscedasticity test, correlation coefficient analysis (r) and coefficient of determination (R2), model feasibility test (F) and partial test (t). Based on all tests, it can be concluded that the workload variable will have a negative and significant effect on employee performance. While the incentive variable has a positive and significant effect on the performance of employees of PT Bank Sumsel Babel Lemabang Sub-Branch.